Ph-NEGATIVE CHRONIC MYELOPROLIFERATIVE DISORDER (IDIOPATHIC MYELOFIBROSIS) – AS ONE OF THE REASONS OF THE BUDD-CHIARI SYNDROME. CLINICAL CASE OF A YOUNG PATIENT - Maria Dmitrievna Sanatko (Mediterranean Journal of Hematology and Infectious Diseases)
Aim. To show the peculiarity of clinical manifestation,diagnostic and therapeutic approach of misdiagnosed chronic myeloproliferative disorder (CMPD), which has